2012
DOI: 10.1073/pnas.1113505109
|View full text |Cite
|
Sign up to set email alerts
|

Whole lifespan microscopic observation of budding yeast aging through a microfluidic dissection platform

Abstract: Important insights into aging have been generated with the genetically tractable and short-lived budding yeast. However, it is still impossible today to continuously track cells by high-resolution microscopic imaging (e.g., fluorescent imaging) throughout their entire lifespan. Instead, the field still needs to rely on a 50-y-old laborious and time-consuming method to assess the lifespan of yeast cells and to isolate differentially aged cells for microscopic snapshots via manual dissection of daughter cells fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
281
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 206 publications
(291 citation statements)
references
References 28 publications
10
281
0
Order By: Relevance
“…However, we were unable to observe any CR-induced lifespan extension using the microfluidic dissection platform. This discrepancy between the two methods cannot be explained by differences in medium, the absence of temperature cycles or by a general inability of the microfluidic dissection platform to generate lifespan extension, because we previously demonstrated that the microfluidic platform generates identical RLS data for several longevity mutants as the classical dissection method [e.g., median RLS of 32 vs. 34 buds for fob1Δ and 13 vs. 13 buds for sir2Δ (22)]. Thus, apparently, CR-induced lifespan extension also depends on subtle, yet unknown, differences between the methods used to determine RLS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, we were unable to observe any CR-induced lifespan extension using the microfluidic dissection platform. This discrepancy between the two methods cannot be explained by differences in medium, the absence of temperature cycles or by a general inability of the microfluidic dissection platform to generate lifespan extension, because we previously demonstrated that the microfluidic platform generates identical RLS data for several longevity mutants as the classical dissection method [e.g., median RLS of 32 vs. 34 buds for fob1Δ and 13 vs. 13 buds for sir2Δ (22)]. Thus, apparently, CR-induced lifespan extension also depends on subtle, yet unknown, differences between the methods used to determine RLS.…”
Section: Discussionmentioning
confidence: 99%
“…RLS was determined using a microfluidic dissection platform (22,37) and an inverted fluorescence microscope (Eclipse Ti-E; Nikon Instruments). The microscope was placed in an incubator (Life Imaging Services) for cultivation at 30°C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations